A novel tool for assessing pediatric emergency care in low- and middle-income countries: a pilot study - Sonia Y. Jarrett; Andrew Redfern; Joyce Li; Camilo E. Gutierrez; Priyanka Patel; Olurotimi Akinola; Michelle L. Niescierenko (International Journal of Emergency Medicine)
Abstract Background Globally, most children seek emergency care at general rather than specialized pediatric emergency departments. There remains significant variation in the provision of pediatric emergency care, particularly in resource-constrained settings. The objective of this study is to pilot a self-assessment tool to evaluate pediatric emergency care capabilities in low- and middle-income country (LMIC) hospitals on the African Continent. Methods This was a prospective cross-sectional descriptive study using a convenience sample of sub-Saharan African hospitals. The assessment tool was developed by operationalizing the technical contents of existing standards and guidelines from international bodies including the World Health Organization and International Federation of Emergency Medicine. The pilot was conducted at emergency departments located across different regions on the African continent. Descriptive statistics were used to evaluate different domains of pediatric emergency care capabilities including pediatric triage, protocols, staffing, training, equipment, consumables, and medicines. Results Sixteen hospitals with emergency departments completed the assessment tool (participation rate of 76%). The hospitals were in nine different countries across four regions of sub-Saharan Africa. National/academic hospitals comprised 56.3% of the participating hospitals. The majority, 44%, of these hospitals saw pediatric patient volumes of 2,000–4,999 patients per year. Dedicated pediatric triage spaces and resuscitation spaces were available at 37.5% and 56.3%, respectively. Formal pediatric resuscitation guidelines were used at 62.5%. Doctors on the self-assessment teams came from primarily pediatrics and general practitioner training backgrounds (both 68.8%). Basic respiratory and airway support equipment (e.g. oxygen, bag-valve mask devices) were available in all participating hospitals, whereas advanced airway equipment (e.g. pediatric intubation equipment) was available in 37.5% of hospitals. Most medicines from the World Health Organization Essential Medicines list were available at participating hospitals. Conclusions To date, this is the first assessment tool dedicated to the comprehensive evaluation of pediatric emergency care in LMICs. This pilot provides a first approach to evaluate pediatric emergency healthcare capabilities in the hospital setting with future directions to improve the tool based on qualitative feedback.